Political violence as shared terrain of militancy: Red Brigades, social movements and the discourse on arms in the early Seventies. (1st September 2016) - Del Vecchio, Giorgio
ABSTRACT: In this paper, the author inspects the discourses on violence carried out in Italy in the first half of the 1970s by the Red Brigades (BR) and the left-wing social movements. Processes for conceptualizing political violence will be examined, in an attempt to understand whether they represented a sort of shared terrain of militancy and in what way they contributed to defining forms and contents of political militancy, either public or clandestine, leading often to diverse outcomes. The paper engages this matter by interlacing simultaneously three analytical levels: firstly, the historical context and the structural changes affecting Italy starting in the late Sixties; and secondly, the manners in which the BR and the various movement's areas conceptualized the political violence. Finally, the forms will be highlighted in which movements and armed struggle perceived each other. Using documents of the BR and the alternative left-wing press as sources, the aim is to consider the role played by these reciprocal perceptions in the definition of certain collective identities, out of the conviction that such an approach may supply new analytical research tools in order to "de-exceptionalize" terrorism and to understand it as a historical phenomenon.